CONCEPTUAL FRAMEWORK ON CORPORATE SOCIAL RESPONSIBILITIES (CSR) ON BIO WASTE MANAGEMENT IN RURAL AREAS – WITH SPECIAL REFERENCE TO NEIGHBOHOOD PERCEPTION ON HOSPITALS IN PONDICHERRY REGION - Porkodi, T.; Venkatramaraju, D. (International Journal of Psychosocial Rehabilitation, 2020)
Medical care is vital for our life and health, but the waste produced from medical activities represents a real problem of living nature and human world. Improper management of waste generated in health care Hospitals causes a direct health impact on the community particularly those who are living nearby hospital areas. In addition to that, waste created from hospitals affects the health care workers and on the environment each day, relatively large amount of potentially infectious and hazardous waste is generated in the health care hospitals. Indiscriminate disposal of Bio Medical Waste (BMW) or hospital waste and exposure to such waste possess serious threat to environment and to human health that requires specific treatment and management prior to its final disposal. The present study deals with the basic issues relating to biomedical waste, procedure of handling and disposal method of Biomedical Waste Management. Further, the study is conducted among the neighborhoods of the hospitals in Pondicherry area to get their perception on biomedical waste disposal and handling it. It also proposes to create awareness about safe disposing of Bio Medical Waste among the personnel involved in health care unit.